2018
DOI: 10.1186/s13104-018-3417-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of melatonin, α-tocopherol, folic acid, acetyl-l-carnitine and resveratrol for anti-dengue 2 virus activity

Abstract: ObjectiveInfections with the mosquito transmitted dengue virus (DENV) are a significant public health burden in many parts of the world. Despite the introduction of a commercial vaccine in some parts of the world, the majority of the populations at risk of infection remain unprotected against this disease, and there is currently no treatment for DENV infection. Natural compounds offer the prospect of cheap and sustainable therapeutics to reduce the disease burden during infection, and thus potentially alleviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
1
19
0
2
Order By: Relevance
“…Melatonin also has beneficial properties in controlling animal models of West Nile virus ( Ben-Nathan et al, 1995 ) and Semliki Forest virus ( Ben-Nathan et al, 1995 ). Furthermore, melatonin has slight proviral impacts upon dengue virus type-2 infection in HEK293 T/17 cells, but no impact was observed in HepG2 cell ( Paemanee et al, 2018 ). Altogether, antiviral effects of melatonin should be further proved, especially in human studies.…”
Section: Melatonin and Viral Infections: Cellular Signaling And Theramentioning
confidence: 99%
“…Melatonin also has beneficial properties in controlling animal models of West Nile virus ( Ben-Nathan et al, 1995 ) and Semliki Forest virus ( Ben-Nathan et al, 1995 ). Furthermore, melatonin has slight proviral impacts upon dengue virus type-2 infection in HEK293 T/17 cells, but no impact was observed in HepG2 cell ( Paemanee et al, 2018 ). Altogether, antiviral effects of melatonin should be further proved, especially in human studies.…”
Section: Melatonin and Viral Infections: Cellular Signaling And Theramentioning
confidence: 99%
“…Several phytochemical families including polyphenols, flavonoids, alkaloids and curcuminoids have been reported to inhibit flavivirus infection [18,21,22,24,25,26,27]. It has been demonstrated that epigallocatechin gallate (EGCG) from green tea, isoquercitrin (Q3G) and curcumin impair ZIKV and DENV infection [17,18,21,28,29,30]. We described that EGCG acts on the early stage of ZIKV and DENV infection by inhibiting the binding of the virus to the cell surface [12,24,29], whereas Q3G inhibits the internalisation process of ZIKV infection in human cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has been shown to be clinically useful in sepsis (43), where the clinical features parallel those of COVID-19 viral infection; moreover, melatonin has been demonstrated to relieve many of the symptoms of other viral infections (17)(18)(19)(20)(21)48). Given the current worldwide situation and in consideration of evidence-based medicine, the efficacy of melatonin and its high pharmacological safety profile supports its use in the treatment of infectious diseases, such as COVID-19.…”
Section: Melatonin In Covid-19 Outbreak: Treatment In the Hospitalmentioning
confidence: 99%